(untitled) (Islas, 2024)
Introduction: Living conditions and the main activity from which the resources for their financial support come are vital to know the wellbeing of a rural family. This research aimed to characterize the social and economic status of 98 peasant families in the municipalities of Ábrego, Bochalema, Bucarasica, Los Patios, Pamplonita and Villa Caro in Norte de Santander. Methods: A non-experimental quantitative research was carried Surveys were applied to inquire about the socioeconomic conditions of the families favored by an agroecological project. Results: The data collected were: age, sex, years living on the farm, occupation, financial support, children raise, parent’s role, living place, the material used to build it, public services, the roads quality and the living conditions that are shown in the graphics descriptions allow to evidence the agricultures’ manner have to develop their family and community activities, their education, how they prepare their food, the transport means they use, and roads types. These aspects are important in individual development before the characterization. Conclusions: This research has obtained relevant data about those aspects and the lacks that homes analyzed in the six rural municipalities have.